2019
DOI: 10.1681/asn.2018080852
|View full text |Cite
|
Sign up to set email alerts
|

Exostosin 1/Exostosin 2–Associated Membranous Nephropathy

Abstract: BackgroundIn membranous nephropathy (MN), which is characterized by deposition of immune complexes along the glomerular basement membrane (GBM), phospholipase A2 receptor (PLA2R) and thrombospondin type 1 domain–containing 7A are target antigens in approximately 70% and 1%–5% of cases of primary MN, respectively. In other cases of primary MN and in secondary MN, the target antigens are unknown.MethodsWe studied 224 cases of biopsy-proven PLA2R-negative MN and 102 controls (including 47 cases of PLA2R-associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
226
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 230 publications
(261 citation statements)
references
References 25 publications
7
226
2
4
Order By: Relevance
“…1 EXT1 and EXT2 have been recently identified as putative antigens in 30% to 40% of secondary autoimmune MN. 8 Thus, PLA2R-associated and EXT1/EXT2-associated MN are the 2 largest subgroups of MN.…”
mentioning
confidence: 99%
“…1 EXT1 and EXT2 have been recently identified as putative antigens in 30% to 40% of secondary autoimmune MN. 8 Thus, PLA2R-associated and EXT1/EXT2-associated MN are the 2 largest subgroups of MN.…”
mentioning
confidence: 99%
“…The most recently identified glomerular proteins involved in MN are EXT1/ EXT2 and NELL-1. Sethi et al [7] identified antibodies against EXT1/EXT2 in the GBM of 21 patients with PLA2R-negative MN using laser microdissection, mass spectrometry and immunohistochemistry. All control cases tested negative for EXT1/ EXT2.…”
Section: Antibodies Against Ext1/ext2 and Nell-1mentioning
confidence: 99%
“…Circulating antibodies against EXT1/EXT2 were not detected in any case, although very few patients had available serum. The authors proposed that EXT1/EXT2 proteins may represent biomarker proteins for MN associated with autoimmune disease rather than target antigens [7].…”
Section: Antibodies Against Ext1/ext2 and Nell-1mentioning
confidence: 99%
See 2 more Smart Citations